Can AI Improve Medication Reconciliation Processes? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Medication reconciliation is a critical safety process in healthcare, designed to prevent adverse drug events by ensuring that a patient's medication list is...
Keywords: AI in Clinical Decision Support; Improve; Medication; Reconciliation; Artificial Intelligence; Machine Learning; Healthcare